Imla' as an Innovative Memorization Method in Qur'an-Hadith Learning - Fahriyan, Wahyu (Abjadia : International Journal of Education, 2023)
This research explores the dual functionality of Imla' as both a writing skill and an innovative memorization method. Employing a qualitative descriptive approach, the study delves into the utilization of Imla' in recording Quranic verses or Hadiths, extending beyond its conventional role in writing skills. The findings reveal that Imla', when integrated into the memorization process, triggers cognitive recording as the teacher recites, mirroring the stages of general Imla'. Success in this method is gauged through fluency, accuracy, and the time required for memorization. While offering advantages such as expedited memorization, the research also acknowledges limitations, emphasizing the need for careful consideration of its suitability across diverse groups and ages. The study's implications underscore the nuanced application of Imla' in educational settings, urging educators to weigh the method's benefits and drawbacks. Recommendations include tailored implementation based on learner characteristics. The research contributes to the understanding of pedagogical approaches within the Quran-Hadith subject, emphasizing the broader utility of Imla' beyond conventional writing skills. Overall, this work enriches educational discourse and provides valuable insights for curriculum development and instructional practices